Crop-livestock intensification in the face of climate change: exploring opportunities to reduce risk and increase resilience in southern africa using an integrated multi-modeling approach - Masikati, Patricia; Crespo, Olivier; Descheemaeker, Katrien K.; Walker, S.; Homann-Kee Tui, Sabine; Claessens, Lieven; Famba, S.; Rooyen, Andre F. van; Gama, A.; Lennard, C. (2013)
Teams of crop, economic, and climate scientists in Southeastern Africa are exploring opportunities to reduce risk and increase resilience in Southern Africa using an integrated multi-modeling approach. The project characterizes selected mixed farming systems in Southern Africa in terms of biophysical and socio-economic characteristics, develops and evaluates crop-livestock management and climate change adaptation strategies that increase food production, agro-diversity and economic returns, and explores the interactions and synergies of increased diversity and integration and their contribution to reduce risk and increase system resilience. The project will increase understanding of challenges and opportunities in the current mixed farming systems of Southern Africa for better targeting of interventions to increase systems resilience and reduce climate-induced risk. It will also improve understanding of the interactions and synergies of production system components, such as which combinations bring about profitable production systems and how to use these to facilitate development along sustainable pathways.